Hydrothermal Activity at the Ultraslow‐Spreading Mohns Ridge: New Insights From Near‐Seafloor Magnetics. (3rd December 2019) - Lim, Anna; Brönner, Marco; Johansen, Ståle Emil; Dumais, Marie‐Andrée
Abstract: Hydrothermal circulation is a process fundamental to all types of mid‐ocean ridges that largely impacts the chemical and physical balance of the World Ocean. However, diversity of geological settings hosting hydrothermal fields complicates the exploration and requires thorough investigation of each individual case study before effective criteria can be established. Analysis of high‐resolution bathymetric and magnetic data, coupled with video and rock samples material, furthers our knowledge about mid‐ocean‐ridge‐hosted venting sites and aid in the interpretation of the interplay between magmatic and tectonic processes along the axial volcanic ridges. The rock‐magnetic data provide constraints on the interpretation of the observed contrasts in crustal magnetization. We map the areal extent of the previously discovered active basalt‐hosted Loki's Castle and inactive sediment‐hosted Mohn's Treasure massive sulfide deposits and infer their subsurface extent. Remarkably, extinct hydrothermal sites have enhanced magnetizations and display clear magnetic signatures allowing their confident identification and delineation. Identified magnetic signatures exert two new fossil hydrothermal deposits, MT‐2 and MT‐3. The Loki's Castle site coincides with negative magnetic anomaly observed in the 2‐D magnetic profile data crossing the deposit. First geophysical investigations in this area reveal the complexity of the geological setting and the variation of the physical properties in the subsurface. Key Points: We present first geophysical observations from the basalt‐hosted active hydrothermal site Loki's Castle, situated at the axial volcanic ridge Sediment‐hosted extinct hydrothermal site Mohn's Treasure, located at the ridge flank, is associated with magnetization high Magnetic data analysis reveals two new fossil hydrothermal sites in the vicinity of the Mohn's Treasure